Characterization and efficacy against carbapenem-resistant Acinetobacter baumannii of a novel Friunavirus phage from sewage - Wang, Zhitao; Yang, Xue; Wang, Hui; Wang, Shuxian; Fang, Ren; Li, Xiaotian; Xing, Jiayin; Wu, Qianqian; Li, Zhaoli; Song, Ningning (Frontiers in Cellular and Infection Microbiology, 2024)
Carbapenem-resistant Acinetobacter baumannii (CRAB) has become a new threat in recent years, owing to its rapidly increasing resistance to antibiotics and new effective therapies are needed to combat this pathogen. Phage therapy is considered to be the most promising alternative for treating CRAB infections. In this study, a novel phage, Ab_WF01, which can lyse clinical CRAB, was isolated and characterized from hospital sewage. The multiplicity of infection, morphology, one-step growth curve, stability, sensitivity, and lytic activity of the phage were also investigated. The genome of phage Ab_WF01 was 41, 317 bp in size with a GC content of 39.12% and encoded 51 open reading frames (ORFs). tRNA, virulence, and antibiotic resistance genes were not detected in the phage genome. Comparative genomic and phylogenetic analyses suggest that phage Ab_WF01 is a novel species of the genus Friunavirus, subfamily Beijerinckvirinae, and family Autographiviridae. The in vivo results showed that phage Ab_WF01 significantly increased the survival rate of CRAB-infected Galleria mellonella (from 0% to 70% at 48 h) and mice (from 0% to 60% for 7 days). Moreover, after day 3 post-infection, phage Ab_WF01 reduced inflammatory response, with strongly ameliorated histological damage and bacterial clearance in infected tissue organs (lungs, liver, and spleen) in mouse CRAB infection model. Taken together, these results show that phage Ab_WF01 holds great promise as a potential alternative agent with excellent stability for against CRAB infections.